PS-B02-7: THE LONG NON-CODING RNA CAREN IMPROVES CARDIAC DYSFUNCTION IN AGED MICE. (January 2023) - Sato, Michio; Miyata, Keishi; Kadomatsu, Tsuyoshi; Node, Koichi; Oike, Yuichi
Abstract : Background: Heart failure (HF) is the predominant cause of hospitalization and amongst the leading causes of death in developed countries. Especially, the prevalence of HFpEF is increasing and its prognosis is not improving. Our understanding of HFpEF pathophysiology is incomplete and optimal treatment remains uncertain. Under such circumstance, recently, it has been reported that some lncRNAs expressed in heart play important roles in cardiac development and disease. Methods and Results: Using a gene trapping approach in mouse embryonic stem cells, we identified Caren (for cardiomyocyte-enriched noncoding transcript), a cytoplasmic lncRNA abundantly expressed in cardiomyocytes. Caren overexpression in cardiomyocytes activated mitochondrial biogenesis by upregulating of Tfam protein and attenuated TAC-induced activation of Ataxia Telangiectasia Mutated (ATM), a key regulator of DNA Damage Response (DDR). Moreover, TAC operated mice treated with AAV6-Caren relieved reduction of fractional shortening (%FS) and improved dilatation of left ventricular. Next, proteomics analysis revealed that Histidine triad nucleotide-binding protein1 ( Hint1 ) which activates the ATM-DDR pathway was reduced in Caren transgenic mice. Moreover, 24-month-old WT mice treated with AAV6- Caren diminished systolic and dilatation capacity were improved. And electron microscopy analysis revealed that mitochondrial cristae were restored and the numbers of mitochondria were increased in the heart of 24-month-old WT mice treated with AAV6-Caren compared with the mice treated with AAV6- GFP as control. Conclusion: A cytoplasmic lncRNA Caren improves not only systolic function but also diastolic function in failing / aged heart by suppressing the ATM-DDR pathway and activating mitochondrial bioenergetics.